Land surface response to climate change forcing over Southern Africa - Shannon, Debbie Anne (Department of Environmental and Geographical Science, 2014)
The land surface is important to the climate system for the exchanges of moisture, momentum and heat. Momentum, radiation, and sensible and latent heat fluxes between the atmosphere and the surface will likely affect atmospheric dynamics, temperature, precipitation and humidity fields (Sato et ai., 1989). These may subsequently feed back into the land surface processes as part of a cyclical system. Therefore it is evident that our livelihood is largely dependent on interactions and exchanges between the land surface and climate system (Henderson-Sellers et ai., 1993) and it is thus essential that we gain a better understanding of the interactive sensitivity. This is of particular relevance in the context of the portended future global climate change. In the present study the interactions between the land surface and the atmosphere are considered over the southern African region. This region has a climate showing a high degree of spatial and temporal variability, most notably with rainfall. Regional climates are characterised by summer, winter and all-year-round rainfall. There are steep vegetation gradients and a wide range of vegetation types adapted to suit the variable climate. These factors, combined with the societal implications of changes in the climate and land surface systems, make southern Africa a challenging and important study domain for examining the sensitivity between the different elements of the atmosphere and biosphere. This research makes use of a biosphere model driven by climate change data derived from a general circulation model (GCM). Regions susceptible and sensitive to changes on an annual and seasonal basis are identified and examined. The thesis comprises 8 chapters. The first chapter, Chapter 1, provides some background information on climate change, biosphereatmosphere interactions, GCMs and transient simulations, vegetation models and vegetation representation over southern Africa. This chapter also sets out the research objectives. The following chapter, Chapter 2, introduces the atmospheric GCM model data from the Hadley Centre Model (HadCM2) used in the analysis. The chapter additionally provides a detailed description of the biosphere model, the Integrated Biosphere Simulator (IBIS). Chapter 3 examines the Hadley Centre HadCM2 GCM input data used in driving the biosphere model, while Chapter 4 presents the input forcing data and configuration of the IBIS model. In Chapter 5 the results of the IBIS model simulation are examined on the annual scale and in Chapter 6 the results are examined on the seasonal scale. Some of the implications of climate change are considered in Chapter 7. This chapter also places the HadCM2 GCM model data used in driving IBIS into the context of the latest emissions scenarios. In the final chapter, Chapter 8, an overview summary is provided and conclusions are drawn.